Enabling silicon-on-silicon photonics with pedestalled Mie resonators. Issue 30 (24th July 2018) - Garín, M.; Solà, M.; Julian, A.; Ortega, P.
Abstract : Pedestalled Mie resonators, made entirely of crystalline silicon, stand optically separated from the substrate enabling all-dielectric silicon-on-silicon nanophotonic applications. Abstract : High-refractive-index Mie resonators are regarded as promising building blocks for low-loss all-dielectric nanophotonic applications. To avoid the otherwise excessive damping and loss of symmetry such devices typically need to be implemented over a low-index substrate, which hampers their integration in many practical applications. In this paper we propose a new photonic structure consisting of silicon-on-silicon spheroidal-like resonators, each one supported by a slim silicon pedestal that makes the micro-cavities stand optically separated from the substrate while providing both mechanical stability and electrical contact with the substrate. These structures are produced in high-quality monocrystalline Si and their size and arrangement can be precisely controlled through standard lithography. We demonstrate that such structures present an optical performance similar to the one achieved with low-index substrates, opening new avenues for developing novel hybrid photonic/electronic devices.